Qualidade fisiológica e sanitária de sementes de arroz com diferentes graus de umidade, tratadas com fungicida - Silva, Clarissa Santos da (2007)
This work was conducted to evaluate the quality of rice seeds treated whit fungicide in different moisture contents during of stored period. Were used two rice seeds lots, cv EL PASO 144, produced in Pelotas/RS during 04/05. For the formularization of fungicide, were additioned 10mL (1%), 20mL (2%) e 30mL (3%) of water in mixed with fungicide Carboxin/Thiram (300mL/ 100Kg of seeds). Same water percentages, without addition of the fungicide, besides one control, had constituted the seven treatments. The seeds were stored in hermetic recipient during eight months period. The quality of seeds was submitted to moisture determination, standard germination, vigor and health. Biochemical evaluation of the seeds was obtained by the technique of electrophoresis of enzymatic systems, being evaluated the activity of the enzymes Acid Phosphates, Alcohol Dehydrogenize, Glutamate Oxalacetate Transaminase, Esterase and a- amylase. The statistic model was of randomizes completely blocks with three replications. The benefic effect of fungicide on physiological quality are evident immediately after the treatment of seeds. The results indicate the germination and vigor reduction of treated seeds increase after 60 days of storage. The fungicide used in treatments of seeds is efficient in reduction of the fungi associates on the rice seeds. Wasn t possible to identify the effect of fungicide in the expression of enzymes of viable seeds.